Energy management strategy for standalone DC microgrid system with photovoltaic/fuel cell/battery storage. (January 2023) - Gugulothu, Ramesh; Nagu, Bhookya; Pullaguram, Deepak
Abstract: Standalone DC microgrids often have challenges in energy management for a long time horizon due to uncertain renewable energy sources and volatile loads. This paper presents a centralized energy management strategy(EMS) for a standalone DC microgrid with solar PV, fuel cells, and a battery energy storage system (BESS). The proposed EMS method is designed to improve the longevity of BESS, reliability, and reduce the hydrogen intake. In the proposed EMS, the PV system de-rating method is used to overcome the deep charging of battery under low-demand conditions. The fuel cell power supply is varied using a reverse sigmoidal function of the Batterys state of charge (SoC). This improves the hydrogen fuel efficiency and also helps in minimizing deep discharge of the battery under heavy loading conditions. The centralized EMS is fed with load power, battery SoC, and individual source power information. Consequently, the EMS provides decisive commands to the individual source local controller to control the respective output power. The efficacy of the proposed EMS under multiple operating conditions is evaluated in both simulation environment and on a hardware prototype of a DC microgrid. Highlights: Hybrid photovoltaic/fuel cell/battery bank system supplying DC grid system Effective energy management strategy (EMS) Seamless transition of BESS is achieved between charging and discharging. Fuel cell output variation based on battery bank SoC